Web Based Academic Data Management System for Higher Education - Sitha, Nur Syifa'u; Batubara, Raihan Syafawi; Khodijah, Siti (Raskha Media Group, 2026)
The scholarly publishing ecosystem has experienced significant transformation in recent years, influencing how scientific knowledge is produced, evaluated, and disseminated. Central to this system is the peer-review process, which serves as a fundamental mechanism for maintaining research quality, credibility, and methodological rigor. This study aims to analyze the key components of the contemporary scholarly publishing environment, including peer-review practices, editorial governance, publication models, ethical standards, scientific writing competencies, and the global dissemination of research. The study employs a qualitative descriptive approach using a systematic literature review method. Relevant academic sources were collected from reputable databases such as Scopus, Web of Science, and Google Scholar. The collected literature was analyzed using thematic analysis to identify major patterns and themes related to the functioning and evolution of scientific publishing. The results indicate that peer review continues to play a critical role in ensuring research reliability, although challenges such as reviewer shortages and increasing submission volumes persist. Editorial governance and transparent evaluation procedures are essential for maintaining publication standards and credibility. Additionally, the growth of open access and hybrid publishing models has improved the accessibility of research outputs but also introduced financial and ethical considerations. The findings further highlight the importance of scientific writing competence and adherence to ethical guidelines in improving manuscript acceptance and research integrity. Moreover, disparities in language, resources, and institutional support continue to influence the global visibility of research. Overall, the study emphasizes the need for collaborative efforts among authors, reviewers, editors, and institutions to strengthen the sustainability, transparency, and inclusiveness of the scholarly publishing ecosystem.